The Long-term Outlook and Risks in Advanced Countries. (May 2015) - Robinson, David
This article seeks to provide a broad overview of the long-term growth outlook for advanced countries, taking into account also the impact and legacies of the Great Moderation and the Great Recession. The article explores their role in the global economy going forward and the key policy challenges that they face, with a particular emphasis on the implications for developing countries. The starting point for this analysis is a brief summary of the short-term outlook for advanced countries and the likely legacies of the Great Recession. Then, the article sets out a baseline scenario for long-term global growth, drawing on the results of the Centennial long-term growth model. In this scenario, global trade would significantly increase and the gap in size in financial markets in emerging and advanced economies would narrow. To achieve these outcomes, advanced economies face challenges, including demographic transition, slow growth, and large fiscal imbalances. To mitigate these risks, advanced countries will need to accelerate and consolidate structural reforms and develop credible medium-term fiscal frameworks. To a certain extent, developing countries need to reduce their reliance on advanced economies to achieve the outcomes described in the baseline scenario; they should boost domestic sources of growth and strengthen their economies against external shocks. This does not preclude international cooperation, however. While some slowdown in financial globalization in particular may be necessary and appropriate to reduce risks to financial stability, there are significant risks that this could go too far. This, in turn, can only reinforce the importance of strengthened multilateral cooperation in the long term.